Fatores críticos de sucesso em implantações de sistemas de suporte a decisão em departamentos de planejamento e controle da produção: estudos de caso - Delle Piagge, Ricardo Magnani (2018)
Looking for competitiveness in global market, companies have been investing efforts: developing new products; changing ways of produce in order to reduce costs; and getting better quality on delivery (quality, velocity and flexibility). That is a route necessary to aim competitiveness to some companies, but to others, it is a survivor path. In the middle of all that movement, the production, planning and control areas (PPCs) are always affected, it raises the complexity of the system that has to be planned, scheduled and controlled. The past few years, in order to minimize the effects on PPCs area, companies have been investing great quantities of resources (financial, areas and people) in decision support systems (DSSs). DSSs are systems capable to help the decision maker, getting data and simulating scenarios online. This kind of investment minimizes the operational work of data collection and let to the manager the responsibility to make decisions. However, like other kinds of implementations that involve people, DSSs implementations have a small percentage of success when some critical factors are not considerate during the software choice, planning of implementation and during the implementation control. With this motivation, this work has the main goal to list a series of critical success factors (CSFs) of this kind of implementation. To ensure the achievement of the goals a systematic review was conducted looking for a literature list of the most cited factors. Afterwards, those factors listed were validated by four cases of study. During the literature review, we listed 27 factors to be considerate on DSSs implementations. 20 of 27 factors were validated by empirical research and belong those factors there were found some that should be considerated as CSFs to implement the software and some that should be considerated also to achieve better performance results. We highlight among then: (i) top management involvement during the implementation and after supporting decisions based on SSD utilization; (ii) interdepartmental cooperation, using at good communication and sharing strategic goals